Predictors of language proficiency and cultural identification in heritage bilinguals - Hayakawa, Sayuri; Chung-Fat-Yim, Ashley; Marian, Viorica (Frontiers in Communication, 2022)
According to the 2020 U.S. Census Bureau, more than 66 million residents over the age of 5 in the United States speak a language other than English at home. Some bilinguals become dominant in the majority language that is spoken in the community as opposed to their native "heritage" language acquired at home. The objective of the current study was to uncover the predictors of language proficiency and cultural identification in different groups of heritage speakers. In our sample, heritage speakers acquired their heritage language first and English second and rated their proficiency in their heritage language lower than in English. We found that English proficiency was most reliably predicted by the duration of heritage language immersion, while heritage language proficiency was most reliably predicted by contexts of acquisition and exposure to both languages. Higher heritage language proficiency was associated with greater heritage language experience through friends and reading, less English experience through family, and later age of English acquisition. The trade-off between heritage language and English language experience was more pronounced for non-Spanish than Spanish heritage speakers. Finally, despite higher proficiency in English, cultural identification was higher with the heritage language, and was predicted by heritage language receptive proficiency and heritage language experience through family and reading. We conclude that self-reported proficiency and cultural identification differ depending on heritage speakers’ native languages, as well as how the heritage language and majority language are acquired and used. Our findings highlight the importance of taking individual language history into consideration when combining different groups of heritage speakers.